2020
DOI: 10.1371/journal.pone.0241264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, regional, and genetic characteristics of Covid-19 patients from UK Biobank

Abstract: Background Coronavirus disease 2019 (Covid-19) has rapidly infected millions of people worldwide. Recent studies suggest that racial minorities and patients with comorbidities are at higher risk of Covid-19. In this study, we analyzed the effects of clinical, regional, and genetic factors on Covid-19 positive status. Methods The UK Biobank is a longitudinal cohort study that recruited participants from 2006 to 2010 from throughout the United Kingdom. Covid-19 test results were provided to UK Biobank starting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
4
35
0
4
Order By: Relevance
“…Currently, there is uncertainty regarding the association between smoking and SARS-CoV-2 infection and severity [ 17 ]. Several studies have reported that current smokers have lower than expected risk for SARS-CoV-2 infection, [ 18 , 19 , 20 , 21 , 22 ] while other studies have suggested that hospitalized smokers with SARS-CoV-2 infection have an increased risk for a severe infection [ 3 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is uncertainty regarding the association between smoking and SARS-CoV-2 infection and severity [ 17 ]. Several studies have reported that current smokers have lower than expected risk for SARS-CoV-2 infection, [ 18 , 19 , 20 , 21 , 22 ] while other studies have suggested that hospitalized smokers with SARS-CoV-2 infection have an increased risk for a severe infection [ 3 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its content in the lung increases upon inflammation and inflammatory cytokines, and consequently, lung levels of C3 are increased in patients with lung diseases 87 . As expected, SARS‐CoV‐2‐infected patients with lung illness have a higher risk to progress to severe disease and die 88 . Since C3 is involved in airway disease and emphysema, 89 COPD patients with high levels of C3 and infected with SARS‐CoV‐2 may be more susceptible to develop a severe disease that stable COPD patients without exacerbations and treated with anti‐inflammatory therapy 90 …”
Section: Innate Immunitymentioning
confidence: 61%
“…87 As expected, SARS-CoV-2-infected patients with lung illness have a higher risk to progress to severe disease and die. 88 Since C3 is involved in airway disease and emphysema, 89 COPD patients with high levels of C3 and infected with SARS-CoV-2 may be more susceptible to develop a severe disease that stable COPD patients without exacerbations and treated with anti-inflammatory therapy. 90 Polycarpou et al 91 have an exciting approach to managing complement and the deleterious effect of the innate immune response in COVID-19 patients.…”
Section: Complementmentioning
confidence: 99%
“…Most of these findings are consistent with those of other published studies. 2,3 Compared with individuals who were not SCT carriers, SCT carriers had similar COVID-19 positivity rates but higher COVID-19 mortality rates overall among Black individuals (Table 1). For Black individuals, the positivity rates were 19.7% (14/71) and 21.1% (167/791) for subjects with SCT and without SCT (P 5 0.96).…”
Section: Resultsmentioning
confidence: 99%
“…1 This finding is supported by United Kingdom Biobank (UKB) studies, which found significantly higher positive rates among Black individuals even after adjusting for biological, behavioral, and socioeconomic factors. 2,3 Additionally, evidence shows that individuals with chronic conditions such as cardiovascular disease, diabetes, chronic respiratory disease, hypertension, and sickle cell disease (SCD) are particularly vulnerable to more severe COVID-19 disease. 1,4 The intersection of race and SCD makes it important to consider their impact on COVID-19.…”
Section: Introductionmentioning
confidence: 99%